223k views
3 votes
D

Click an item in the list or group of pictures at the bottom of the problem and, holding the button down, drag it into the
correct position in the answer box, Release your mouse button when the item is place. If you change your mind, drag
the item to the trashcan Click the trashcan to clear all your answers.
Solve by factoring
x2 + 6.9. Hint. This is a double root.
3
9
12131415161718
VI
NEXT QUESTION
© ASK FOR HELP
TURN ITIN
© 2014 Glynlyon, Inc. All rights reserved
TERMS OF USE

D Click an item in the list or group of pictures at the bottom of the problem and-example-1

1 Answer

3 votes

Answer:

–3 and –3

Explanation:

x² + 6x = – 9

Rearrange

x² + 6x + 9 = 0

Multiply the first term i.e x² and last term i.e 9 together. The result is 9x².

Next, we shall find two factors of 9x² such that when we add them together, the result will be the same as the 2nd term i.e 6x in the expression above.

The factors are 3x and 3x.

Next, we shall replace 6x with 3x and 3x in the equation above as shown below:

x² + 6x + 9 = 0

x² + 3x + 3x + 9 =0

Factorise

x(x + 3) + 3(x + 3) = 0

(x + 3)(x +3) = 0

x + 3 = 0 or x + 3 =

x = – 3 or x = – 3

Therefore, the solutions are –3 and –3

User Johanson
by
5.1k points